RELATIONSHIP BETWEEN VISUAL DISPLAY TERMINAL (VDT) USE DURATION AND DRY EYE SYNDROME AMONG MEDICAL STUDENTS AT MUHAMMADIYAH YOGYAKARTA UNIVERSITY - Annisa'u Syafa'atuddiinul Khaq; Yunani Setyandriana (Medika Kartika : Jurnal Kedokteran dan Kesehatan, 2026)
Dry eye syndrome is a multifactorial condition affecting the ocular surface and is characterized by disruption of tear film homeostasis, inflammation, ocular surface damage, discomfort, and visual disturbances. Its severity is classified as mild, moderate, or severe. One contributing factor is prolonged use of Visual Display Terminals (VDTs), which are electronic devices used to display information. VDT use is categorized as < 3 hours and ≥ 3 hours per day. This study aimed to examine the relationship between VDT use duration and dry eye syndrome among medical students at Muhammadiyah University of Yogyakarta. Primary data for this cross-sectional study were obtained from the Ocular Surface Disease Index (OSDI) questionnaire and a questionnaire assessing computer use. The sample consisted of 223 medical students who met the inclusion and exclusion criteria. Of the 223 respondents, 156 (70%) were female. Severe dry eye syndrome was identified in 112 respondents (50.2%), and blurred vision was the most frequently reported symptom, occurring in 49 respondents (21.9%). Most respondents (94.6%) used VDTs ≥ 3 hours per day. Data analysis demonstrated that VDT use duration was significantly associated with dry eye syndrome (p = 0.009 (p < 0.05)). Participants who used VDTs for ≥3 hours per day had a 1.53-fold higher risk of developing dry eye syndrome than those who used VDTs for <3 hours per day. Keywords: dry eye syndrome, medical students, visual display terminal DOI 10.35990/mk.v9n2.p150-159